Using routers and honeypots in combination for collecting Internet worm attacks - Mohammed, Mohssen M. Z. E.; Pathan, Al-Sakib Khan (CRC Press, Taylor & Francis Group, USA, 2014)
The best way to first define honeypot would be to talk about its history, which we understand as an appropriate sequence of reading and understanding relevant critical information. There are many definitions of honeypot [1]. In other words, there is no clearly standardized definition of honeypot. Different researchers may have their own definitions of what a honeypot is. This fact has created a great deal of confusion and miscommunication. Some think that it is a tool for deception whereas others consider it as a weapon to lure hackers, and still there are others who believe that it is simply another intrusion detection tool. Some believe a honeypot should emulate vulnerabilities. Others see it simply as a jail! There are also some who view honeypots as controlled production systems that attackers can break into. These various viewpoints have caused a lot of misunderstanding about what a honeypot is and thus have caused barriers to realizing their true value.